Regional Language Studies. Newfoundland, Number 22 (1 March 2011) - Cuff, Robert, 1959-; Kirwin, W. J.; Thorburn, Jennifer (Memorial University of Newfoundland. Department of English Language and Literature, 2011)
“Date of this entry” : queries raised by the “1805 Conception Bay Plantations Book” / Robert H. Cuff -- “There’s no place like Petty Harbour” : negation in a post-insular community / Jennifer Thorburn -- The genesis of James Cook’s Australian place-names / William J. Kirwin -- Miscellany / William J. Kirwin.